2004
DOI: 10.1002/pd.910
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum levels of placental proteins after in vitro fertilisation and their implications for prenatal screening

Abstract: Reduced PAPP-A with increased hCG yields an increased risk in screening for foetal trisomy 21. We confirm recently published observations but do not recommend the establishment of normal medians for IVF pregnancies since the extent of the deviations is varying according to the different stimulation protocols and dosages of gonadotrophins used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
4
13
1
Order By: Relevance
“…This is in agreement with most previous studies (6,10,11,14,(17)(18)(19)(20). Some studies have reported the fb-hCG to be increased (13,15,(21)(22)(23). In the largest study to date, Kagan et al (12) found the median fb-hCG was 9% higher in the IVF pregnancies.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This is in agreement with most previous studies (6,10,11,14,(17)(18)(19)(20). Some studies have reported the fb-hCG to be increased (13,15,(21)(22)(23). In the largest study to date, Kagan et al (12) found the median fb-hCG was 9% higher in the IVF pregnancies.…”
supporting
confidence: 89%
“…Also, a functional delay in fetal and placental development and the higher risk of obstetric complications associated with ART can lead to changes in marker concentrations (15,19). Several studies have suggested that exogenous hormone treatment is the main reason for reduced PAPP-A levels (11,15,16,21). In our study, we found that PAPP-A levels were reduced in hormonally stimulated IVF/ICSI pregnancies, but we also found that PAPP-A levels were decreased in nonstimulated FET cycles.…”
supporting
confidence: 41%
See 1 more Smart Citation
“…Most studies showed decreased PAPP-A levels in ART pregnancies combined with unaltered levels of fβ-hCG [9,13,14,16,17,20,21] increased fβ-HCG levels [12,22,23,24] or even decreased fβ-hCG levels [15,25]. Two studies reported only an increase in fβ-hCG levels [10,26], and some studies reported no changes in maternal serum values in ART pregnancies [11,18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In ART pregnancies maternal serum marker levels change during the first trimester affecting the risk assessment for DS [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies.…”
Section: Introductionmentioning
confidence: 99%